A neonatal network's approach to benchmarking the principles of care of the baby and family experience. (7th June 2011) - Bissell, G; Stewart, D; Prince, R
Abstract : Aim: Benchmarking neonatal services alongside family representatives is a pinnacle of good practice and one that neonatal networks' performance may be measured against. Methods: An audit specific to benchmark Principle 3 was developed from the Toolkit for High Quality Neonatal Services (2009) and administered to 11 neonatal service providers in a staged schedule of unit visits. Results: The results offered a broad outline of the current care provision of services and the facilities being offered in all the units across the Network. The benchmark identified a number of issues requiring further address; some being minor and relatively cost neutral while other aspects required major work with large financial-resource implications. In some cases capacity and storage of equipment have taken precedence, thus infringing upon the families welfare and allowing a void of basic facility provision (paucity of sitting area and drink facility). Nevertheless across the network examples of innovation and good practice can be cited and there remain opportunities to share and pool resources. Summary: By undertaking this benchmark the Yorkshire Neonatal Network has demonstrated a commitment to assessing the progress of its units and the services that are currently being offered to the families and babies. For many neonatal care provider trusts it will indeed be a challenge to demonstrate that procedures are being put into place to bring about changes to enhance the quality and safety of care-facilities being offered to their service users.